Proteomic approach: Identification of Nephotettix virescens vector protein transmitting the tungro virus in rice - WASIS SENOAJI; Bambang Tri Rahardjo; Hagus Tarno (Society for Indonesian Biodiversity, 2021)
Abstract. Senoaji W, Rahardjo BT, Tarno H. 2021. Proteomic approach: Identification of Nephotettix virescens vector protein transmitting the tungro virus in rice. Biodiversitas 22: 2750-2755. As a vector of tungro virus, Nephotettix virescens is one primary pest in rice cultivars. Associated Rice Tungro Spherical Virus provides a helper component for Rice Tungro Bacilliform Virus acquisition produced the severe symptoms in rice. The vector proteins encoded by the virus become a poorly understood transmission of plant viruses, particularly in semi-persistent mechanisms. It is essential to develop new molecules to interrupt the transmission mechanism of plant viruses by insect vectors. This study aimed to detect the helper proteins in vectors with proteomics. Protein separation was performed using SDS-PAGE, and then was identified by the Liquid Chromatography-Mass Spectrometry (LC-MS/MS) to find the candidate proteins. The result showed that actin was identified in N. virescens as responsible protein that related to transmitting tungro viruses into the plant.